Population genomics of rainforest mountain frogs (Anura: Limnodynastidae: Philoria) severely impacted by the Australian megafires - Shengyao Lin; David Newell; Nicola J. Mitchell; Stephen C. Donnellan; Michael Mahony; Liam J. Bolitho; Renee A. Catullo (Conservation Genetics, 2025)
The 2019/20 Australian megafires impacted numerous species, including six of the seven montane frog species from the genus Philoria , which are restricted to the top of mountain habitats across eastern Australian Gondwana Rainforest. Using single nucleotide polymorphisms, we examined the population structure and genetic diversity of the six Philoria species to inform conservation management and assess their capacity for post-fire recovery. Narrow-range species were confirmed as a single population for management purposes, while P. kundagungan , P. loveridgei , and P. sphagnicolus exhibit marked genetic differentiation between populations, indicating strong allopatric differentiation among populations isolated on separate mountaintops, suggesting limited natural dispersal ability. We further identify high-value genetic populations in these structured species. Populations that were heavily impacted by the fires, such as P. pughi and P. knowlesi , may face longer-term threats due to potential declines in adaptive capacity. We recommend prioritising in situ management, genetic rescue, and translocation efforts to bolster resilience in isolated populations. Updated conservation planning and targeted fire buffer management are crucial for the survival of these ancient, regionally endemic frogs in a rapidly changing climate.

Mitochondrial genomes reveal low genetic diversity in snow leopards - Shiqing Wang; Haimeng Li; Yinping Tian; Yu Lin; Yingna Zhou; Jan E. Janecka; Yuan Fu; Yue Ma; Zhen Wang; Tianming Lan (Conservation Genetics, 2025)

DNA barcoding of traded shark fins, meat and mobulid gill plates in Singapore uncovers numerous threatened species - Benjamin J. Wainwright; Yin Cheong Aden Ip; Mei Lin Neo; Jia Jin Marc Chang; Chester Zhikai Gan; Naomi Clark-Shen; Danwei Huang; Madhu Rao (Conservation Genetics, 2018)

Effects of emerging infectious diseases on host population genetics: a review - Donald T. McKnight; Lin Schwarzkopf; Ross A. Alford; Deborah S. Bower; Kyall R. Zenger (Conservation Genetics, 2017)

Population genetic diversity and geographical differentiation of MHC class II DAB genes in the vulnerable Chinese egret (Egretta eulophotes) - Wei Lei; Wenzhen Fang; Xiaoping Zhou; Qingxian Lin; Xiaolin Chen (Conservation Genetics, 2016)

Limited diversity associated with duplicated class II MHC-DRB genes in the red squirrel population in the United Kingdom compared with continental Europe - Keith T. Ballingall; Angeline McIntyre; Zhenzhen Lin; Naomi Timmerman; Erik Matthysen; Peter W.W. Lurz; Lynsey Melville; Amy Wallace; Anna L. Meredith; Claudia Romeo; Lucas A. Wauters; Anthony W. Sainsbury; et al. (Conservation Genetics, 2016)

Genetic population structure of the masked palm civet Paguma larvata, (Carnivora: Viverridae) in Japan, revealed from analysis of newly identified compound microsatellites - Tomo Inoue; Yayoi Kaneko; Koji Yamazaki; Tomoko Anezaki; Shuuji Yachimori; Keiji Ochiai; Liang-Kong Lin; Kurtis Jai-Chyi Pei; Yen-Jean Chen; Shih-Wei Chang; Ryuichi Masuda (Conservation Genetics, 2012)

Phylogenetic position of a threatened stag beetle, Lucanus datunensis (Coleoptera: Lucanidae) in Taiwan and implications for conservation - Chung-Ping Lin; Jen-Pan Huang; Yat-Hung Lee; Ming-Yu Chen (Conservation Genetics, 2011)

Two genetic divergence centers revealed by chloroplastic DNA variation in populations of Cinnamomum kanehirae Hay - Dai-Chang Kuo; Chia-Chia Lin; Kuo-Chieh Ho; Yu-Pin Cheng; Shih-Ying Hwang; Tsan-Piao Lin (Conservation Genetics, 2010)

New polymorphic microsatellite markers for bluefin leatherjacket (Navodon septentrionalis Gunther, 1877) - Gen-Bo Xu; Song-Lin Chen; Yong-Sheng Tian (Conservation Genetics, 2010)

Habitat fragmentation affects genetic diversity and differentiation of the Yarkand hare - Yonghua Wu; Lin Xia; Qian Zhang; Qisen Yang (Conservation Genetics, 2010)

Isolation and characterization of 30 novel polymorphic microsatellite loci from Japanese halfbeak, Hyporhamphus sajori (Temminck et Schlegel, 1846) - Shi-Chao Xing; Gen-Bo Xu; Guan-Pin Yang; Shan-Shan Liu; Xiao-Lin Liao; Yong-sheng Tian; Song-Lin Chen (Conservation Genetics, 2009)

Isolation and characterization of 12 polymorphic microsatellite markers from ladyfish (Elops saurus Linnaeus) - Zhen-Xia Sha; Shi-Chao Xing; Chang-Wei Shao; Yong-Sheng Tian; Xiao-Lin Liao; Song-Lin Chen (Conservation Genetics, 2009)

Isolation and characterization of microsatellites in Chinese white olive (Canarium album) and cross-species amplification in Canarium pimela - Xin Zhang; Wan-Hui Ye; Hong-Lin Cao; Zheng-Feng Wang; Hao Shen; Ju-Yu Lian (Conservation Genetics, 2009)

Isolation and characterization of polymorphic microsatellite loci from black snapper Sebastodes fuscescens (Houttuyn) - Jing-Feng Yang; Li-Li Zhao; Chang-Wei Shao; Xiang-Shan Ji; Xiao-Lin Liao; Song-Lin Chen (Conservation Genetics, 2009)

Isolation and characterization of polymorphic microsatellite loci from fat greenling (Hexagrammos otakii) - Song-Lin Chen; Gui-Dong Miao; Chang-Wei Shao; Yong-Sheng Tian; Xiaolin Liao (Conservation Genetics, 2009)

Isolation and characterization of 10 polymorphic microsatellite loci from small yellow croaker (Pseudosciaena polyactis) - Song-Lin Chen; Shi-Chao Xing; Gen-Bo Xu; Xiaolin Liao; Jing-Feng Yang (Conservation Genetics, 2009)

Isolation and characterization of microsatellite markers for Cycas hainanensis C. J. Chen (Cycadaceae) - Min Zhang; Zheng-Feng Wang; Shu-Guang Jian; Wan-Hui Ye; Hong-Lin Cao; Peng Zhu; Ling Li (Conservation Genetics, 2009)

Isolation and characterization of polymorphic microsatellite loci from black sea bass (Centropristis striata) and cross-species amplification - Song-Lin Chen; Lili Zhao; Chang-Wei Shao; Xiaolin Liao; Yong-Sheng Tian (Conservation Genetics, 2009)

Twelve polymorphic microsatellite loci from a dinucleotide-enriched genomic library of Japanese Spanish mackerel (Scomberomorus niphonius) - Shi-Chao Xing; Gen-Bo Xu; Xiao-Lin Liao; Guan-Pin Yang; Song-Lin Chen (Conservation Genetics, 2009)

Isolation and characterization of 12 microsatellite loci from cutlassfish (Trichiurus haumela) - Jin-Zhen Bi; Chang-Wei Shao; Gui-Dong Miao; Hong-Yu Ma; Song-Lin Chen (Conservation Genetics, 2009)

Isolation and characterization of polymorphic microsatellite loci from bluefin leatherjacket (Navodon septentrionalis Gunther, 1877) - Gen-Bo Xu; Yong-Sheng Tian; Xiao-Lin Liao; Song-Lin Chen (Conservation Genetics, 2009)

Isolation and characterization of 15 microsatellite loci from Caridina gracilipes (Atyidae, Decapoda) - Chiao-Chuan Han; Cheng-Sheng Chang; Tzen-Yuh Chiang; Ping-Han Chung; Hung-Du Lin (Conservation Genetics, 2009)

Isolation and characterization of ten polymorphic microsatellite in the endangered tree Erythrophleum fordii oliv - Peng Zhu; Wan-Hui Ye; Zheng-Feng Wang; Hong-Lin Cao; Min Zhang; Ling Li; Wei Xiao (Conservation Genetics, 2009)

Isolation and characterization of polymorphic microsatellite loci from a repeat-enriched genomic library of stone flounder (Kareius bicoloratus) and cross-species amplification - Yong-Sheng Tian; Gui-Dong Miao; Chang-Wei Shao; Xiao-Lin Liao; Song-Lin Chen (Conservation Genetics, 2009)

Isolation and characterization of polymorphic microsatellite loci in Candidia barbata (Cyprinidae) using PCR-based isolation of microsatellite arrays (PIMA) - Tzen-Yuh Chiang; Yu-Min Ju; Lee-Shing Fang; Chung-Jian Lin (Conservation Genetics, 2009)

Development of polymorphic microsatellite markers from barfin flounder (Verasper moseri) and their cross-species amplification - Gui-Dong Miao; Chang-Wei Shao; Xiao-Lin Liao; Hong-Yu Ma; Yong-Sheng Tian; Song-Lin Chen (Conservation Genetics, 2009)

Development of twelve polymorphic microsatellite loci in polyploid endangered Omphalogramma vincaeflora Franch. (Primulaceae) - Yuan Huang; Yong Li; Xiao Hu; Xue-Jun Ge; Chang-Qin Zhang; Chun-Lin Long (Conservation Genetics, 2009)

Eighteen novel polymorphic microsatellite loci developed from the Père David’s deer (Elaphurus davidianus) - Hai-Long Wu; Xiao-Wei Ni; Lin-Yuan Zhang; Jin-Shi Xia; Zhen-Yu Zhong; Guo-Ping Zhu; Qiu-Hong Wan (Conservation Genetics, 2008)

Isolation and characterization of microsatellite loci in the commercially important mudshrimp Austinogebia edulis (Upogebiidae) using PCR-based isolation of microsatellite arrays (PIMA) - Tzen-Yuh Chiang; Hung-Du Lin; Tin-Yam Chan; Cheng-Yu Hung; Feng-Jiau Lin (Conservation Genetics, 2008)

Genetic diversities of the giant panda (Ailuropoda melanoleuca) in Wanglang and Baoxing Nature Reserves - Wei He; Ling Lin; Fujun Shen; Wenping Zhang; Zhihe Zhang; Emily King; Bisong Yue (Conservation Genetics, 2008)

Isolation and characterization of microsatellite loci in the endangered freshwater fish Varicorhinus alticorpus (Cyprinidae) - Tzen-Yuh Chiang; Teh-Wang Lee; Feng-Jiau Lin; Kuo-Hua Huang; Hung-Du Lin (Conservation Genetics, 2008)

Isolation and characterization of 11 polymorphic microsatellite loci from Fatsia polycarpa (Araliaceae), an element of evergreen forests in Taiwan - Chi-Chun Huang; Kuo-Hsiang Hung; Tsai-Wen Hsu; Kuo-Hsiung Wang; Chi-Yung Lin; Tzen-Yuh Chiang (Conservation Genetics, 2008)

Ventral coloration differentiation and mitochondrial sequences of the Chinese Cobra (Naja atra) in Taiwan - Hua-Ching Lin; Shou-Hsien Li; Jonathan Fong; Si-Min Lin (Conservation Genetics, 2008)

Identification and characterization of EST-SSRs and cpSSRs in endangered Cycas hainanensis - Zheng-Feng Wang; Wan-Hui Ye; Hong-Lin Cao; Zhong-Chao Li; Shao-Lin Peng (Conservation Genetics, 2008)

Characterization and cross-species amplification of microsatellites from the endangered Hawksbill turtle (Eretmochelys imbricate) - Grace Lin; Alex Chang; Hon Wah Yap; Gen Hua Yue (Conservation Genetics, 2008)

Characterization of novel microsatellite loci in the great leaf-nosed bat, Hipposideros armiger and cross-amplification in other related species - T. T. Guo; P. Y. Hua; L. K. Lin; S. Y. Zhang (Conservation Genetics, 2008)

Isolation and characterization of microsatellite loci in the endangered freshwater fish Pararasbora moltrechti (Cyprinidae) using PCR-based isolation of microsatellite arrays (PIMA) - Hung-Du Lin; Teh-Wang Lee; Fang-Jiao Lin; Chung-Jian Lin; Tzen-Yuh Chiang (Conservation Genetics, 2008)

A reliable, non-invasive PCR method for giant panda (Ailuropoda melanoleuca) sex identification - Xiao Xu; Ling Lin; Zhihe Zhang; Fujun Shen; Liang Zhang; Bisong Yue (Conservation Genetics, 2008)

Characterization of seven genomic and one dbEST-derived microsatellite loci in the river mangrove Aegiceras corniculatum (Myrsinaceae) - Guo-Qing Chen; Lin-Feng Li; Gang Hao; Su-Hua Shi; Xue-Jun Ge (Conservation Genetics, 2008)

Development of thirteen microsatellite loci for Impatiens lateristachys (Balsaminaceae) - Lin-Feng Li; Guo-Qing Chen; Yong-Ming Yuan; Xue-Jun Ge (Conservation Genetics, 2008)

Development of ten microsatellite loci for Gentiana crassicaulis (Gentianaceae) - Yong Li; Lin-Feng Li; Guo-Qing Chen; Xue-Jun Ge (Conservation Genetics, 2007)

Novel polymorphic microsatellites for studying genetic diversity of red Asian arowanas - G. H. Yue; Z. Y. Zhu; G. Lin; L. C. Lo; F. Feng (Conservation Genetics, 2006)

Microsatellite Loci from Lanyu Scops Owl (Otus elegans botelensis) and their Cross-Species Application in Four Species of Strigidae - Yu-Cheng Hsu; Shou-Hsien Li; Yao-Sung Lin; Lucia Liu Severinghaus (Conservation Genetics, 2006)

Additional microsatellite loci for the endangered St. Vincent Parrot, Amazona guildingii - M. A. Russello; K. Lin; G. Amato; A. Caccone (Conservation Genetics, 2006)

Mitochondrial DNA Diversity in two populations of Taiwanese macaque (Macaca cyclopis) - Jui-Hua Chu; Yao-Sung Lin; Hai-Yin Wu (Conservation Genetics, 2005)

Isolation and characterization of microsatellite loci in Acrossocheilus paradoxus (Cyprinidae) using PCR-based isolation of microsatellite arrays (PIMA) - Kui-Ching Hsu; Jiang-Ping Wang; Xiang-Lin Chen; Tzen-Yuh Chiang (Conservation Genetics, 2004)